Predicting the elastic properties and deformability of red blood cell membrane using an atomistic-continuum approach - Adesola Ademiloye (Proceedings of the International MultiConference of Engineers and Computer Scientists 2016, 2016)
This paper employs the gradient theory to study the elastic properties and deformability of red blood cell (RBC) membrane using the first-order Cauchy-Born rule as an atomistic-continuum hyperelastic constitutive model that directly incorporates the microstructure of the spectrin network. The well-known Cauchy-Born rule is extended to account for a three-dimensional (3D) reference configuration. Using the strain energy density function and the deformation gradient tensor, the elastic properties of the RBC membrane were predicted by minimizing the potential energy in the representative cell. This extended formulation was then coupled with the meshfree method for numerical modeling of the finite deformation of the RBC membrane by simulating the optical tweezer experiment using a self-written MATLAB code. The results obtained provide new insight into the elastic properties and deformability of RBC membrane. In addition, the proposed method performs better when compared with those found in literature in terms of prediction accuracy and computation efficiency.